Motivasi Siswa terhadap Penerapan Senam Aerobik di Sekolah Semi Militer SMA Titian Teras Jambi - Riska Sinaga; Ahmad Muzaffar; Mohd. Adrizal (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to determine the level of student motivation towards the implementation of aerobic exercise as a physical fitness activity at the semi-military school of SMA Negeri Titian Teras H. Abdurrahman Sayoeti Jambi. The low variation of physical activity in the routine morning exercise program which has been dominated by Healthy Indonesian Children's Exercise is the background for this study. The method used is descriptive quantitative with a survey approach. The study population was all grade X students of SMA Negeri Titian Teras Jambi, with a sample of 100 students selected through a purposive sampling technique based on their active participation in morning exercise activities. The research instrument was a questionnaire with a Likert scale of 1–5 consisting of 40 valid statements, with a Cronbach's Alpha reliability value of 0.982. The results showed that the average overall score was 103.67 out of an ideal score of 175 (59.24%), which placed the level of student motivation in the sufficient to high category. A total of 91.0% of students were in the moderate to high motivation category, with 49.0% in the moderate category, 34.0% in the high category, and 8.0% in the very high category. Only 9.0% of students were in the low motivation category, and none were in the very low category. These findings indicate that aerobic exercise receives a positive response from students and has great potential to be developed as a superior fitness program in semi-military educational environments.